Sustainable management of potato tuber moths using eco-friendly dust formulations during storage in the Andean highlands - Villanueva Spelucín, Alex (2026)
Postharvest losses caused by potato tuber moths severely impact storage in the Andean highlands, where reliance on synthetic insecticides poses sustainability and safety concerns. This study evaluated eco-friendly alternatives for protecting stored seed tubers of the widely adopted cultivar INIA 302 Amarilis in Cajamarca, Peru. In two storage facilities, a completely randomized block design compared four treatments: Bacillus thuringiensis plus talc (Bt-talc), talc, agricultural lime, and wood ash against an untreated control. Powders were applied at 50 g per 10 kg of tubers, and incidence, severity of damage, and live larvae were assessed over 150 days. Bt–talc consistently achieved the lowest damage. Incidence in Cochapampa was 16.8% ± 6.2 with Bt-talc, compared with 58.1% ± 3.9 in the control; in Sulluscocha, incidence was 25.5% ± 4.8 and 64.2% ± 3.0 for Bt-talc and the control, respectively. A similar pattern was observed for moth-damage severity in both localities. Live larvae per unit were also markedly lower with 1.3 ± 0.3 (Cochapampa) and 1.6 ± 0.6 (Sulluscocha) under Bt–talc. A single dusting with Bt–talc, or alternatively agricultural lime, offers effective, accessible, and sustainable control of potato tuber moths in high-Andean storage.